TRPM4 expression is associated with activated B-cell subtype and poor survival in diffuse large B-cell lymphoma - Loo, S; Ch'ng, E; Salleh, M; Banham, A; Pedersen, L; Møller, M; Green, T; Wong, K (Wiley, 2017)
Aims Transient receptor potential channel melastatin 4 (TRPM4) is an ion channel that regulates influx of calcium cations (Ca2+). Recent studies suggest that TRPM4 is an oncoprotein and its upregulated transcript level has been reported in diffuse large B-cell lymphoma (DLBCL). We aim to investigate TRPM4 protein expression pattern in non-malignant tissues and DLBCL cases, and its association with clinico-demographical parameters and survival in DLBCL. Methods and results Analysis of publicly-available DLBCL microarray datasets showed that TRPM4 transcripts were upregulated in DLBCL compared to normal germinal centre B (GCB) cells, were more highly expressed in the activated B-cell-like DLBCL (ABC-DLBCL) subtype, and higher TRPM4 transcripts conferred worse overall survival (OS) in R-CHOP-treated DLBCL cases (P<0.05). Our immunohistochemical analysis showed that TRPM4 was expressed in various human tissues but not in normal B cells within lymphoid tissues (reactive tonsil, lymph node and appendix). TRPM4 protein was present in 26% (n=49/189) of our cohort of R-CHOP-treated DLBCL cases and this was significantly associated with more aggressive clinical parameters including higher LDH, ECOG scores or stage (P<0.01 for each of the parameter) and the ABC-DLBCL subtype (P=0.016). TRPM4 positivity conferred significantly worse OS (P=0.004) and PFS (P=0.005). Worse OS remained significantly associated with TRPM4 positivity in multivariate analysis including higher international prognostic index (IPI) or the non-GCB DLBCL phenotype (P<0.05). Conclusions TRPM4 protein expression is upregulated in DLBCL cases compared to non-malignant B cells with preferential expression in ABC-DLBCL cases, and it confers significantly poorer DLBCL patients’ outcomes.